Possible algal origin and life cycle of Ediacaran Doushantuo microfossils with dextral spiral structure. (January 2014) - Zhang, Xi-Guang; Pratt, Brian R.
Abstract : In Ediacaran shallow-water dolomites of the Doushantuo Formation (ca. 570 Ma) of southern China, scarce phosphatized microfossils consisting of clusters of coil-like spheroids called Spiralicellula bulbifera and co-occurring spherical forms with helically arranged holes named Helicoforamina wenganica are interpreted to belong to the same taxon because both have a similar relative abundance and both, uniquely in the assemblage, exhibit a consistent dextral spiral feature—the oldest known fossil examples of fixed asymmetry. Thus, we interpret them as different stages of sexual and asexual life cycles in which the spiral structure was maintained throughout most of the developmental phases. While they can be placed with the acritarchs, we suggest they are a chlorophycean green alga, and like many Ediacaran macrofossils, may represent an extinct clade. This is compatible with the shoal-water marine depositional environment in which they lived, as it would have favored photosynthetic organisms over others kinds of encysting non-metazoan protists. This setting militates against their interpretation as putative embryos which has been put forward for a variety of forms co-occurring in the microfossil assemblage. The multiple affinities of the strikingly diverse biota remain far from resolved, but algal origins warrant further consideration.